2013
DOI: 10.1089/jwh.2012.3667
|View full text |Cite
|
Sign up to set email alerts
|

Confusion About Pap Smears: Lack of Knowledge Among High-Risk Women

Abstract: Knowledge about the purpose of the Pap smear remains low. Findings underscore the significant need for clear and consistent messages among high-risk women regarding the prevention of cervical cancer and other reproductive health conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 16 publications
5
24
0
Order By: Relevance
“…Pap test abnormality as an all-inclusive phrase for women’s health problems conflated pelvic exams, STI testing and Pap smears. Similar results have been reported by numerous studies over many years, in various populations, and without apparent improvement over time [6, 1117]. In conducting focus groups with an earlier sample of incarcerated women, we also found that women perceived all gynecological health exams to include a Pap test and that all gynecological problems were reflected as an abnormality in this test [18].…”
Section: Discussionsupporting
confidence: 88%
“…Pap test abnormality as an all-inclusive phrase for women’s health problems conflated pelvic exams, STI testing and Pap smears. Similar results have been reported by numerous studies over many years, in various populations, and without apparent improvement over time [6, 1117]. In conducting focus groups with an earlier sample of incarcerated women, we also found that women perceived all gynecological health exams to include a Pap test and that all gynecological problems were reflected as an abnormality in this test [18].…”
Section: Discussionsupporting
confidence: 88%
“…Unfortunately, as illustrated in this study, a dearth of knowledge and awareness is still common among women [20,21]. Thus, future research should incorporate health literacy as a critical component in cervical cancer prevention programming efforts.…”
Section: Discussionmentioning
confidence: 85%
“…Thus, future research should incorporate health literacy as a critical component in cervical cancer prevention programming efforts. Health literacy efforts could greatly assist in increasing knowledge and awareness about cervical cancer and its prevention modalities; understanding how and when screening should be obtained; evaluating personal health history and other risk factors; and, communicating decision-making processes and related feelings with healthcare providers, families and friends [20]. As stated by the SCT, a person and their corresponding health behaviors are greatly influenced by their physical and social environments [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with recent research revealing wide spread confusion about cervical cancer risk and Pap tests among a population of high risk women. 42 Such findings suggest that HIV care providers may not be effectively communicating cervical cancer prevention and early detection messages to their clients as all participants had a regular source for health care, and most reported being adherent to their medical appointments. What is not known from these findings is whether the health care clinics where the women received care have specific protocols that address cervical cancer risk among HIV-infected women and their needs for information and education.…”
Section: (Age 48 No Pap Test)mentioning
confidence: 98%